Drying's Impact on Antioxidant Compound Levels in Curcuma heyneana Valeton & Zijp. (Temu Giring) - Agustin Yumita; Ni Putu Ermi Hikmawanti; Heksa Mu’adah; Endang Hanani (Biology, Medicine, & Natural Product Chemistry, 2026)
One plant in the genus Curcuma that exhibits potential as a natural antioxidant is Curcuma heyneana Valeton & Zijp., commonly known as temu giring. This species contains phenolic and flavonoid compounds. The objective of this research was to quantify the phenolic and flavonoid content, as well as assess the antioxidant activity of fresh and dried rhizomes. The extraction methods employed were infusion and decoction. Phenolic content was measured using the colorimetric method with the Folin-Ciocalteu reagent, while flavonoid content was determined using the AlCl3 reagent. Antioxidant activity was evaluated using the FRAP method. The highest phenolic content was observed in the oven-dried decoction extract (EDOD) at 6.258 mg GAE/g, and the highest total flavonoid content was also found in this EDOD at 2.899 mg QE/g. The most potent antioxidant activity among the test samples was exhibited by this EDOD, with a value of 12.064 mol FeEAC/g. The results indicate that higher drying temperatures correlate with increased phenolic and flavonoid levels in the temu giring rhizome, consequently influencing the antioxidant activity in the sample.